State capability and prospects for close co-ordination: Considerations for industrial policy in Africa - Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Recent research highlights the considerable potential of industrial policy to support structural transformation in sub-Saharan Africa. Given the importance of the state in industrial policy, this paper considers the implications for these discussions of recent work on state fragility. It argues that weaknesses in state capacity in the region can be expected to severely limit the likelihood of successful industrial policy in a number of countries - indeed, over a half of them, if we believe standard metrics. It concludes that more attention should be paid in work on industrial policy to the systematic study of weak state capacity and strategies to address the challenges it poses, including 'islands of excellence'.
Keywords: L50; O25; O40; O57; 330; industrial policy; fragile states; weak states; state capacity; sub-Saharan Africa; structural transformation